PENINGKATAN HASIL BELAJAR PENJUMLAHAN PECAHAN MENGGUNAKAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK DI KELAS IV SD - Juwita, Ira (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research background by the fact the sum of fractions learning teachers still teach the traditional way with the meaning of the word is not linking student learning to real life. Thus resulting in poor learning outcomes and have not reached the Chief Engineer student set is 70. The purpose of this study to describe the form of planning, implementation, and improvement of learning outcomes by using a sum of fractions of Realistic Mathematics Education (RME). In this study the authors used qualitative and quantitative approaches. From the data analysis studies concluded that the approach of Realistic Mathematics Education (RME) in the sum of fractions of learning can improve student learning outcomes. Kata kunci : hasil belajar ; penjumlahan pecahan; pendekatan pendidikan matematika realistik (PMR ).